Analisis Strategi Pengembangan Wisata Edukasi Melalui Pendekatan Blue Ocean Strategi (Studi pada Wisata Taman Pendidikan Purbasari Pancuran Mas) - Aisah Nur Fadilah; Dhini Amalia Putri; Fanisa Yuliana; Na’imatul Aulia; Saidah Saidah; Yoiz Shofwa Shafrani (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study applies the Blue Ocean Strategy (BOS) approach to examine the development of educational tourism at Purbasari Pancuran Mas Educational Tourism Park. The method used is descriptive qualitative, with data collection techniques through documentation, interviews, and direct observation in the field. The analysis was conducted by identifying tourism potential, examining competitive factors, and applying the four-step BOS framework (ERRC), namely eliminate, reduce, raise, and create. The results show that Purbasari Pancuran Mas has great potential as an environmentally based educational tourism destination, particularly in freshwater ecosystems. These advantages are evident in the variety of attractions, service quality, and ongoing innovations. The implementation of BOS is carried out by eliminating less valuable practices, reducing irrelevant elements, improving the quality of services and education, and creating new innovations to provide added value, increase competitiveness, and open wider market opportunities.